The Index to the Ledger: Some Historical Notes. - Yamey, Basil S. (The Accounting Review, 1980)
ABSTRACT: This article examines the discussion and illustration of the ledger index in some early treatises on bookkeeping and accounts, and comments on the economizing of effort and paper in the early practice of bookkeeping.